Effect of Renal Impairment on the Pharmacokinetics and Pharmacodynamics of Tofogliflozin (A SELECTIVE SGLT2 Inhibitor) in Patients with Type 2 Diabetes Mellitus - Ikeda, Sachiya; Takano, Yasuki; Schwab, Dietmar; Portron, Agnes; Kasahara-Ito, Nahoko; Saito, Tomohisa; Iida, Satofumi (Drug Research, 2019)
Purpose Tofogliflozin is an orally available selective inhibitor of sodium-glucose co-transporter 2 for treatment of type 2 diabetes mellitus (T2DM). Two studies were conducted to evaluate the effect of renal impairment on pharmacokinetics and pharmacodynamics of tofogliflozin.Methods The studies were: 1) single dose study in T2DM patients with normal renal function and mild, moderate and severe renal impairment, and 2) multiple dose study for 24 weeks in T2DM patients with normal renal function and moderate renal impairment.Results Renal function did not have a clinically relevant effect on the PK of tofogliflozin. Urinary glucose excretion up to 24 h after administration of tofogliflozin (UGE24h) decreased with decreasing glomerular filtration rate. Lowering UGE24h resulted in waning glycemic control but not body weight reduction.Conclusions Single and multiple administrations of tofogliflozin were generally well tolerated in T2DM patients with various renal functions. As far as investigated here, these studies indicate no dose adjustment is required for patients with renal impairment.
Keywords: tofogliflozin; renal impairment; urinary glucose excretion; type 2 diabetes mellitus